Principles of digital image synthesis - Glassner, Andrew S. (Morgan Kaufmann Publishers, 1995)
Image synthesis, or rendering, is a field of transformation: it changes geometry and physics into meaningful images. Because the most popular algorithms frequently change, it is increasingly important for researchers and implementors to have a basic understanding of the principles of image synthesis. Focusing on theory, Andrew Glassner provides a comprehensive explanation of the three core fields of study that come together to form digital image synthesis: the human visual system, digital signal processing, and the interaction of matter and light. Assuming no more than a basic background in calculus, Glassner transforms his passion and expertise into a thorough presentation of each of these disciplines, and their elegant orchestration into modern rendering techniques such as radiosity and ray tracing.